Shakespeare in London [videorecording] : the life and times of the Real William Shakespeare. (Camarillo, CA : Goldhil Entertainment, 1999)
Follow William Shakespeare through 16th Century and 17th Century London as he created many of the most important work ever written. This incredible period is a source of continued fascination and was portrayed in 1998's Academy Award winning Best Picture.
Keywords: Shakespeare, William, 1564-1616